2019
DOI: 10.25134/erjee.v7i2.1526
|View full text |Cite
|
Sign up to set email alerts
|

Digital Comic: An Innovation of Using Toondoo as Media Technology for Teaching English Short Story

Abstract: This study investigates the use of ToonDoo as media technology for teaching English short story. ToonDoo as the newest technology for creating comic or picture story is very beneficial helping teacher to creatively provide innovative strategy providing better classroom environment for the English learners, especially for those studying English short story. As the invented prose narrative shorter than a novel dealing with a few characters, short story can give an important content raising cultural awareness, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 6 publications
(9 reference statements)
2
43
0
1
Order By: Relevance
“…Literature [4] believes that programmed language is "a part of automatic or semi-automatic memory reserve, even through the screening mechanism of dividing these words, they are still automatically stored". Literature [5] believes that spoken language is a series of words that people habitually use together.…”
Section: Related Workmentioning
confidence: 99%
“…Literature [4] believes that programmed language is "a part of automatic or semi-automatic memory reserve, even through the screening mechanism of dividing these words, they are still automatically stored". Literature [5] believes that spoken language is a series of words that people habitually use together.…”
Section: Related Workmentioning
confidence: 99%
“…For this purpose, the students needed to turn on their audio and video features so that lecturer and other students could hear and see the explanation. The use of digital comics had been proven effective in improving students' ability in retelling story (Fatimah et al, 2019) . The assistance of digital comics may reduce students' axiety in speaking.…”
Section: The Utilization Of Digital Comics In Grammar Classmentioning
confidence: 99%
“…They considered Webtoon as a student-learning media which provided many features to pursue the students' goal, increased motivation, and were applicable at any situation. On the other hand, Fatimah et al (2019) found out that ToonDoo was an advantageous application to help teachers provide authentic platform and alluring media in teaching short story. In addition, the use of ToonDoo had enhanced teacher's professional development, which perceived through teacher's creativity in producing digital comics.…”
Section: Introductionmentioning
confidence: 99%
“…In virtual reality, through diversified interactions such as vision, sound, touch, and operation, users can apply perception experience and cognitive processing capabilities to interact with objects in virtual reality just like in the real world and observe natural changes in the world. Virtual reality uses three elements to construct a virtual reality context [2]: (1) immersion, allowing users to have an "immersive" feeling and blending into the simulated virtual world; (2) interactivity, users passing sensory stimulation and reaction interact with and give feedback to the virtual situation; the system responds to the user in the shortest time and allows the user to feel the response in a simulated situation; (3) conceptual, virtual reality is a fictitious simulated situation. In addition to feeling the sound and light stimulation, you can also conceive of situational design and object attributes and express intangible abstract concepts in concrete forms.…”
Section: Introductionmentioning
confidence: 99%